Severe Anemia Is Associated with Intestinal Injury in Preterm Neonates - Ozcan, Beyza; Aydemir, Ozge; Isik, Dilek Ulubas; Bas, Ahmet Yagmur; Demirel, Nihal (American Journal of Perinatology, 2020)
Objective A temporal relationship has been reported between necrotizing enterocolitis, anemia, and red blood cell transfusion (RBCT) in preterm neonates. However, the mechanism underlying this association is not clearly defined. Intestinal (I-) and liver (L-) fatty acid binding proteins (FABPs) have been proposed as plasma markers for the detection of acute intestinal injury. This study aimed to investigate the effect of anemia and RBCT on intestinal injury in preterm neonates by measuring serum I-FABP and L-FABP levels.Study Design A prospective cohort study including preterm neonates with gestational age <32 weeks and/or birth weight <1,500 g and requiring erythrocyte transfusions for anemia after day 15 of life was conducted. Stable growing preterm infants with hemoglobin values ≥ 10 g/dL were taken as controls. I-FABP and L-FABP levels of the neonates with anemia were compared with levels of the control group. In addition, pretransfusion I-FABP and L-FABP levels of the neonates with anemia were compared with posttransfusion levels.Results In total, 39 infants transfused for anemia and 20 controls were enrolled. L-FABP levels were significantly higher in neonates with anemia compared with controls (p < 0.001), whereas I-FABP (p = 0.695) was not different. L-FABP and I-FABP levels were similar before and after transfusion in neonates with anemia. L-FABP levels before transfusion were negatively correlated with pretransfusion hemoglobin levels (p < 0.001).Conclusion Anemia is associated with intestinal injury documented by increased L-FABP levels in preterm infants, and this injury is more severe with lower hemoglobin levels.
Keywords: anemia in the preterm neonate; fatty acid binding proteins; intestinal injury; necrotizing enterocolitis; red blood cell transfusion